MODEL MANAGEMENT TRAINING OF CLASSROOM ACTION RESEARCH BASED ON ISLAMIC MODERATE FOR ISLAMIC EDUCATION - Nur Cholid, Masrukhi, Rusdarti, AT Sugito (Pascasarjana Universitas Wahid hasyim Semarang, 2017)
AbstractEfforts which done to increase teacher’s quality such as givingtraining about curriculum, learning method, and continuing studyfor those who have not under-graduate program yet. But thoseefforts seem did not work well maximally to increase processquality and learning result. For those reason, Action Researchtraining is needed to increase profesional competence of IslamicEducation teacher. This research was conducted with the aim toproduce a product, that is the management model of ClassroomAction Research based on Islamic moderate for Islamic EducationTeachers, which will be packaged in the form of a manual ofclassroom action research training model for Islamic educationteachers handbook. This study used the Research Development(Research and Development) approach, which was preceded byqualitative descriptive method as the first step in this research. Theresults showed that the development of the classroom actionmanagement training model was carried out in accordance withthe development procedure, which included preliminary research,analysis, production / development, and revision, while evaluationof the product was developed in accordance with the developmentevaluation procedure.Keywords: model of training management; Classroom ActionResearch (PTK); Islamic moderate